2011
DOI: 10.1590/s0103-50532011000500016
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and composition of propolis obtained by different methods of extraction

Abstract: Extratos etanólicos de própolis obtidos a partir de diferentes concentrações de própolis e com álcool hidratado com diferentes teores de álcool/água foram analisados. A ação antioxidante destes extratos foi determinada através da captura do radical livre 1,1-difenil-2-picril-hidrazila (DPPH•) e do poder de redução férrico (FRAP) utilizando o complexo férrico-tripiridiltriazina (Fe 3+ -TPTZ). O teor de compostos fenólicos totais e a quantificação de flavonóides também foram verificados e obtidos por espectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
17

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 15 publications
3
72
0
17
Order By: Relevance
“…Castro et al (2007) found total phenol compound values in propolis produced by A. mellifera bees similar to the values found in propolis produced by A. mellifera bees from the city of Santa Maria of Tocantins. However, Rodríguez et al (2012) and Cottica et al (2011) found higher values for propolis produced by this species. No studies were found showing total phenol concentrations as high as that from the propolis produced by M. fasciculata -city of Santa Maria.…”
Section: Discussionmentioning
confidence: 60%
“…Castro et al (2007) found total phenol compound values in propolis produced by A. mellifera bees similar to the values found in propolis produced by A. mellifera bees from the city of Santa Maria of Tocantins. However, Rodríguez et al (2012) and Cottica et al (2011) found higher values for propolis produced by this species. No studies were found showing total phenol concentrations as high as that from the propolis produced by M. fasciculata -city of Santa Maria.…”
Section: Discussionmentioning
confidence: 60%
“…Although propolis has shown beneficial effects in human and animal health by acting as an antioxidant (COTTICA et al, 2011), antimicrobial (FALCÃO et al, 2014 and antiviral (SCHNITZLER et al, 2009), for example, there is no consensus regarding its beneficial effects on poultry performance. Improvements in poultry performance by propolis and its products have been demonstrated in several studies (DENLI et al, 2005;GALAL et al, 2008;SHALMANY;SHIVAZAD, 2006;TEKELI et al, 2011), whereas Eyng et al (2014 showed a decrease in body weight gain and feed intake when broilers from 1 to 7-d of age fed ethanolic propolis extract.…”
Section: Discussionmentioning
confidence: 99%
“…Propolis has important biological properties such as antioxidant (COTTICA et al, 2011), immunomodulatory (FREITAS et al, 2011;YUAN et al, 2012), anti-inflammatory (HORI et al, 2013), antiviral (SCHNITZLER et al, 2009) and antibacterial (FALCÃO et al, 2014) which are mainly attributed to its flavonoids and polyphenols. These compounds are extracted from propolis for use in human medicine where solvents are employed, typically grain alcohol, in order to obtain its ethanol extract.…”
Section: Introductionmentioning
confidence: 99%
“…DPPH EC50 value between 47 and 160 μg mL -1 for Brazilian hydroalcoholic propolis extracts have been reported [23]. The values between 65 and 79% of DPPH inhibition for Canadian propolis ethanol extracts at 210 μg mL -1 was also reported [24].…”
Section: Figurementioning
confidence: 97%